Sticholysin I–membrane interaction: An interplay between the presence of sphingomyelin and membrane fluidity - Pedrera, Lohans (2014)
Sticholysin I (St I) is a pore-forming toxin (PFT) produced by the Caribbean Sea anemone Stichodactyla helianthus belonging to the actinoporin protein family, a unique class of eukaryotic PFT exclusively found in sea anemones. As for actinoporins, it has been proposed that the presence of sphingomyelin (SM) and the coexistence of lipid phases increase binding to the target membrane. However, little is known about the role of membrane structure and dynamics (phase state, fluidity, presence of lipid domains) on actinoporins' activity or which regions of the membrane are the most favorable platforms for protein insertion. To gain insight into the role of SM on the interaction of St I to lipid membranes we studied their binding to monolayers of phosphatidylcholine (PC) and SM in different proportions. Additionally, the effect of acyl chain length and unsaturation, two features related to membrane fluidity, was evaluated on St I binding to monolayers. This study revealed that St I binds and penetrates preferentially and with a faster kinetic to liquid-expanded films with high lateral mobility and moderately enriched in SM. A high content of SM induces a lower lateral diffusion and/or liquid-condensed phases, which hinder St I binding and penetration to the lipid monolayer. Furthermore, the presence of lipid domain borders does not appear as an important factor for St I binding to the lipid monolayer.